Fading into the background: the dark space surrounding Vermeer’s Girl with a Pearl Earring - Vandivere, Abbie; van Loon, Annelies; Callewaert, Tom; Haswell, Ralph; Proaño Gaibor, Art Ness; van Keulen, Henk; Leonhardt, Emilien; Dik, Joris (Heritage science, 2019)
The background of Vermeer’s Girl with a Pearl Earring (c. 1665, Mauritshuis) has, until recently, been interpreted as a flat dark space. The painting was examined in 2018 as part of the research project The Girl in the Spotlight using a combination of micro- and macro-scale analytical techniques. The stratigraphy of the background was determined from samples mounted as cross-sections, and its material composition was analysed using electron microscopy and chromatographic techniques. The underlayer contains mainly charcoal black, and the glaze contains two organic colourants—indigo and weld—and a copper drier. Deterioration of the glaze has made features in the background difficult to discern with the naked eye. Complementary imaging techniques were able to visualise Vermeer’s signature, and the suggestion of folded fabric (possibly a curtain) on the right side of the painting. The distribution of the layer(s) in the background were imaged using: infrared reflectography (900–1100 nm), multi-scale optical coherence tomography scanning, macroscopic X-ray fluorescence and 3D digital microscopy. Vermeer applied the black underlayer vigorously with overlapping brushstrokes that varied in thickness. When he applied the glaze on top, it levelled out to make a smooth flat surface. The visual effect of the background contrasts the figure of the Girl and projects her forward in space, closer to the viewer.